Effects of frying parameters on physical changes of tapioca chips during deep-fat frying. - Vasanti Nair, Chanderan K.; Chee , C. Seow; Sulebele, Guruprasad A. (Wiley, 1996)
The interrelationships of the effects of frying time, oil temperature, and initial moisture content on moisture loss, oil absorption, and linear expansion of a tapioca starch chip half-product during deep-fat frying have been studied. Both oil absorption and linear expansion were affected, in different ways, by moisture loss.